IMPROVING STUDENTS' READING COMPREHENSION THROUGH THE SCANNING TECHNIQUE - Wulandari, Citra Agustya (2014)
The research paper entitled "Improving Students' Reading Comprehension through the Scanning Technique" was aimed to investigate the use of scanning technique in improving students' reading comprehension in a junior high school in Bandung. Thirty one ninth grade students participated in this study. Classroom action research was employed as the research method. The data were gathered from several sources, including observation in each meeting of the cycle and questionnaire. The findings of this study indicated that the average scores in cycle two ( = 83,7) was higher than cycle one ( = 76,2). In addition, the result of students' questionnaire showed that 77% students chose the option "agree" and 33% students chose "strongly agree" to use scanning technique in comprehending report texts. This study is expected to give a contribution to the English teaching. Moreover, the further researchers are suggested to investigate the use of scanning technique in other texts. Key Words : Scanning Technique, Reading Comprehension Penelitian yang berjudul "Meningkatkan Pemahaman Membaca Siswa melalui Tehnik Scanning" ditujukan untuk meneliti penggunaan tekhnik scanning dalam meningkatkan pemahaman membaca pada siswa kelas sembilan di sebuah sekolah mengeah pertama di Bandung. Tiga puluh satu siswa kelas sembilan berpartisipasi dalam penelitian ini. Penelitian Tindakan Kelas digunakan sebagai metodologi penelitian. Data dikumpulkan dari beberapa sumber, diantaranya observasi di setiap siklus pertemuan dan kuesioner. Penemuan dalam penelitian ini menunjukan bahwa nila diharapkan rata-rata siklus kedua ( = 83,7) lebih besar dari siklus pertama ( = 76,2). Selain itu, hasil dari kuesioner siswa menunjukan bahwa 77% siswa memilih pilihan "setuju" dan 33% siswa memilih pilihan "sangat setuju" untuk menggunakan tekhnik scanning dalam memahami teks report. Penelitian ini diharapkan memberikan sebuah kontribusi terhadap pengajaran bahasa Inggris. Selain itu, peneiti selanjutnya disarankan untuk meneliti penggunaan tekhnik scanning pada jenis teks yang lain. Kata Kunci : Tekhnik Scanning, Pemahaman Membaca